Evolutionary dynamics and research hotspots of phage applications against Acinetobacter baumannii infections from the past to the new era - Jiang, Ping; Luo, Xiaoqin; Zhao, Jing; Sun, Jingwei; Su, Zhanhai; Cheng, Peng (Frontiers in Microbiology, 2025)
BackgroundAcinetobacter baumannii is a common hospital pathogen that poses a serious clinical challenge due to its rapidly increasing resistance to antibiotics. Phage therapy has been successfully used to treat antibiotic resistant A. baumannii infections. The aim of this study was to comprehensively assess the current status and trend of research on the application of phages in A. baumannii infections through bibliometric analysis.MethodsStudies on phages and A. baumannii infections were searched in the Web of Science Core Collection database and relevant articles were selected for inclusion in the study based on the inclusion criteria. Bibliometric and visual analysis of the included publications were performed using VOSviewer and CiteSpace software.ResultsA total of 264 studies were included. There is an increasing trend in the number of publications per year from 2010 to 2024. China was the leading country with 35.98% of the total publications. Tzu Chi University and Lin, Nien-Tsung were the most influential institution and author, respectively. The journal with the highest H-index was Frontiers in Microbiology, and Viruses-Basel was the most prolific journal. Antimicrobial Agents and Chemotherapy was the most cited journal. Phages endolysin and phage therapy were found to be the widely researched aspects, biofilm, phage resistance and synergistic effect are recent research hotspots.ConclusionIn the last decade or so, this is the first bibliometric study that systematically describes the research hotspots and development trends on phages in A. baumannii infections. Research hotspots should be given more attention.